THE STRUCTURE AND DEVELOPMENT OF THE DEAD SEA BASIN: RECENT STUDIES - Ben-Avraham Z.; Lazar M. (My University, 2006)
Recent studies on the evolution of the Dead Sea basin have shed light on the intricate tectonic regime of the area. Combined with newly available data from Jordan, a new picture of a symmetrical deep basin is emerging. Salt is prevalent over the entire width of the basin in the south. The original thickness of this layer was calculated to be ̃2 km, but at present it does not exceed 900 m. Crustal studies indicate a difference between the southern and northern basins, which are separated by a large, normal fault. Depth to the basement in the northern basin is estimated to be 6-8 km, while that of the southern basin is 12 km. Relocation of deep earthquakes revealed that the majority of well-constrained micro-earthquakes (M;L ≤ 3.2) occurred at depths much deeper than previously expected (20-32 km). Seismicity and the low value of regional heat flow suggest that the lower crust might be cool and brittle. A lithospheric strength profi le was calculated, indicating a narrow brittle-to-ductile transition at a depth of 31 km. Uplift measurements, submersible studies, and combined geological-geophysical mapping are some of the new techniques applied to the area to solve the complex neotectonic structure. Results indicate that the southern and northern basins are both currently active. In addition to tectonics, activity is also inferred by the presence of salt diapirs, whose uplift or subsidence may be related to current motion along active faults. Discrepancies in earthquake-reoccurrence times may indicate that the main fault in the northern Dead Sea basin, the Jericho fault (also known as the Jordan fault), is segmented, or that earthquakes occur in clusters. One such segment is responsible for the formation of a small subbasin on the northwestern shore of the lake, the Qumran basin, whose complex neotectonic regime includes strike-slip, reverse and normal faulting, folding, right bending splays, and a migrating depocenter. Recent global positioning system measurements provide slip-rates of 2.6-3.8 mm/yr for the current plate motion in this area. An open crack between the seafloor and a sharp bathymetric cliff in the lake provides visual evidence for this motion, while data from shallow seismic surveys present paleoseismic information on this activity. © 2006 Geological Society of America.
Keywords: DEAD SEA; PULL-APART BASINS; RIFT VALLEY; STRIKE-SLIP FAULT